2021
DOI: 10.2298/vsp190402086t
|View full text |Cite
|
Sign up to set email alerts
|

Association of prothrombin, FV Leiden and MTHFR gene polymorphisms in the Montenegrin patients with venous thromboembolism

Abstract: Background / Aim. Polymorphisms of the factor V Leiden (FV G1691A), factor II Prothrombin (FII G20210A) and methylenetetrahydrofolate reductase (MTHFR C677T) genes are the most commonly investigated inherited risk factors for developing venous thromboembolism (VTE). Despite this fact, there is insufficient data regarding their clinical burden and distribution in Montenegrin population. Consequently, the present study aimed to determine the frequency of these polymorphisms in Montenegrin patients with VTE. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…Our study showed that the prevalence of heterozygous F2 20 210G>A and F5 1691G>A polymorphisms in the control fertile population of Montenegrin women was lower (1.1% and 2.1%, respectively) than it was found for the European – Caucasian population, but it was in the range of reported results within different populations. We previously reported a similar prevalence for F2 and F5 heterozygotes (both 2.5%) in the general Montenegrin population,18 but neither the present, nor our previous study showed the presence of variant homozygotes in these genes among general population. The prevalence of F2 20 210G>A and F5 1691G>A heterozygotes among women with RPL and IUFD in our study was lower than reported in the studies that confirmed the association between these polymorphisms and early/late RPL and late non-recurrent PL and IUFD 9 10 19–21.…”
Section: Discussioncontrasting
confidence: 74%
“…Our study showed that the prevalence of heterozygous F2 20 210G>A and F5 1691G>A polymorphisms in the control fertile population of Montenegrin women was lower (1.1% and 2.1%, respectively) than it was found for the European – Caucasian population, but it was in the range of reported results within different populations. We previously reported a similar prevalence for F2 and F5 heterozygotes (both 2.5%) in the general Montenegrin population,18 but neither the present, nor our previous study showed the presence of variant homozygotes in these genes among general population. The prevalence of F2 20 210G>A and F5 1691G>A heterozygotes among women with RPL and IUFD in our study was lower than reported in the studies that confirmed the association between these polymorphisms and early/late RPL and late non-recurrent PL and IUFD 9 10 19–21.…”
Section: Discussioncontrasting
confidence: 74%